Targeting Mitochondria for Cancer Treatment - Ljubava D. Zorova; Polina A. Abramicheva; Nadezda V. Andrianova; Valentina A. Babenko; Savva D. Zorov; Irina B. Pevzner; Vasily A. Popkov; Dmitry S. Semenovich; Elmira I. Yakupova; Denis N. Silachev; Egor Y. Plotnikov; Gennady T. Sukhikh; et al. (MDPI AG, 2024)
There is an increasing accumulation of data on the exceptional importance of mitochondria in the occurrence and treatment of cancer, and in all lines of evidence for such participation, there are both energetic and non-bioenergetic functional features of mitochondria. This analytical review examines three specific features of adaptive mitochondrial changes in several malignant tumors. The first feature is characteristic of solid tumors, whose cells are forced to rebuild their energetics due to the absence of oxygen, namely, to activate the fumarate reductase pathway instead of the traditional succinate oxidase pathway that exists in aerobic conditions. For such a restructuring, the presence of a low-potential quinone is necessary, which cannot ensure the conventional conversion of succinate into fumarate but rather enables the reverse reaction, that is, the conversion of fumarate into succinate. In this scenario, complex I becomes the only generator of energy in mitochondria. The second feature is the increased proliferation in aggressive tumors of the so-called mitochondrial (peripheral) benzodiazepine receptor, also called translocator protein (TSPO) residing in the outer mitochondrial membrane, the function of which in oncogenic transformation stays mysterious. The third feature of tumor cells is the enhanced retention of certain molecules, in particular mitochondrially directed cations similar to rhodamine 123, which allows for the selective accumulation of anticancer drugs in mitochondria. These three features of mitochondria can be targets for the development of an anti-cancer strategy.